PERFORMANCE EVALUATION OF THE HYBRID GEOBAGS AND PU FLATBED SYSTEM AS A SOFT GROUND IMPROVEMENT WORK (Malaysian Journal of Civil Engineering, 2022)
Soft ground is commonly known as a problematic soil foundation, thus required a ground improvement work to be executed. research was carried out to evaluate the performance of the Hybrid Geobag PU flatbed as a proposed remedial work for the failed embankment founded on soft ground in Pulau Betong. Back-analysis of existing embankment was executed using PLAXIS 2D in order to investigate the failure mechanism of the existing embankment. The cause of the embankment failure is due to the excessive consolidation settlement which causes both vertical and horizontal displacements of the . Performance of the proposed remedial works was compared with the conventional design solution of bored pile embankment. Existing embankment has an extreme vertical displacement of 1.87m and horizontal displacement of 0.259m. With the Hybrid Geobag PU flatbed method, the vertical and horizontal displacement reduced to 0.879m and 0.098m respectively. The vertical and horizontal displacement further reduced to 0.099m and 0.030m respectively with bored pile method.